Biogenic synthesis of selenium nanoparticles from Valeriana officinalis extract: A dual approach for environmental remediation and cancer therapy - Fatemeh Nazarzadeh; Saied Navabpour; Zahra Sabouri; Majid Darroudi (Open Ceramics)
This study employed the green synthesis approach to produce Selenium nanoparticles (Se-NPs) using Valeriana officinalis (Valerian) root extract as a biological agent for reduction and stabilization. The phytochemicals present in the extract enabled the generation of stable Se-NPs without the use of toxic chemicals. The nanoparticles underwent extensive characterization using UV–Vis spectroscopy, XRD, FTIR, and TEM images, confirming their structural, morphological, and surface properties. The Se-NPs demonstrated photocatalytic performance, which was confirmed by the efficient photodegradation of Rhodamine B (RhB) dye (98 % after 150 min). Furthermore, biological assays revealed that the nanoparticles exhibited selective cytotoxicity toward cancer B16F0 cells. This dual functionality, photocatalytic degradation, and selective anticancer effect highlight the applicability of Se-NPs in environmental and biomedical fields.